ANALISIS PERTUMBUHAN EKONOMI DAN PENGELUARAN PEMBANGUNAN DI KABUPATEN AGAM - Sufyeti, Sufyeti; Aimon, Hasdi; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2012)
ABSTRACT This study aims to determine and analyze (1) the effect of private investment, labor, and development expenditure to economic growth in Agam regency.(2) the effect of labor, inflation,economic growth and development expenditures in agam regency. This type of of research is descriptive and associative studies. While the data type is documentary data, the source data is secondary data sources and in the form of time series from 1980 to 2009. This study utilize a model of simultaneous equations by means of indirect least square (ILS). Endogeneous variables in this study is economic growth and development expenditrue. While the exsogen variable are private investment,labor and inflation. Based on these results. It is recomended to agam goverment to make regulation for stimulating investor to put investement in agam regency. The method is to simplify the bureaucracy process for investment, and promote that agam regency is a promising region to invest. It is neccessary for agam local government to provide training and education for the workforce in agam regency therefore the workforce will work in accordance with their respective expertise. Keywords: Development expenditure, economic growth, inflation, private investment, labor